The township-based MSME's perspective: Understanding the challenges and benefits associated with DFI Business Development Services in South Africa - Thomas, Tayla (Graduate School of Business (GSB), 2022)
It is universally recognized that micro, small and medium enterprises (MSMEs) are extremely valuable in creating social and economic development. It is for this reason that many countries have adopted MSME development policies as part of their national development strategies. In South Africa, the post-Apartheid government rolled out development policies and established institutions through the Department of Trade and Industries (DTI) with the aim to boost development of previously marginalised MSMEs. Up to 85% of the MSMEs in South Africa are informal and survivalist businesses, the majority of which are based in the townships. 70% of MSMEs in South Africa fail within their first 5-7 years. It is evident that the development of the MSME sector in South Africa is lagging behind, even with the existence of these government-led business development service (BDS) institutions. Against this background, this study sought to explore the benefits and challenges associated with utilising these development services from the perspective of the township-based MSME. The study employed the thematic qualitative analytical technique to analyse primary interview data from 17 township-based MSMEs in South Africa. The study found the main challenges to be a demand-supply mismatch, poor access to finance, lack of aftercare programmes, lack of trust in government services and poor quality and duration of services. In terms of the positives, a demand-supply match was found with the outsourced training, the quality of financial services was found to be advantageous and assistance with regulatory compliance was highly beneficial. Based on the findings, it is recommended that institutions should focus on outsourcing to the specialised and sector-specific incubation hubs rather than utilising inhouse training. Development Finance Institutions (DFIs) should outsource training to specialised townshipbased incubation hubs. Instead of pressurising informal township businesses to formalise, DFIs should aim to support a transition from the traditional informal sector to the modernising informal sector. In terms of government monitoring, policies driven by measurable targets need to be put in place and reviewed on a quarterly basis. Other recommendations include consultations, mentorship provision in clusters, an alumni network, feedback surveys, government service procurement backed by legislation, the adoption of e-procurement, the use of public-private partnerships (PPPs), an effective monitoring system, an ongoing entrepreneurship campaign and the adoption of the integrated model.